Few winners, many losers: the COVID-19 pandemic’s dramatic and unequal impact on independent news media - Nielsen, R; Cherubini, F; Andi, S (Reuters Institute for the Study of Journalism, 2020)
To better understand the impact COVID-19 has had on independent news media, we worked with members of the Independent News Emergency Relief Coordination (INERC) to collect data from across the globe. Our survey responses and interviews suggest that the COVID-19 pandemic will have a dramatic and unequal impact on independent news media, with few winners, and many losers. Our sample of respondents is not representative, but if the organisations covered here are indicative of the wider situation in the global news industry, newspapers alone are looking at a loss that could amount to a decline of thirty billion dollars in expected revenues in 2020. Such a drop would have dramatic consequences for the number of journalists employed, especially at the local level and in poorer communities and countries. At the same time, we also find that a significant minority of independent news media are finding a way through the crisis, and some, often smaller and medium-size online newsrooms, have seen stable or even growing revenues.